Nanobiomaterials in medical imaging applications of nanobiomaterials - Grumezescu, Alexandru Mihai (Amsterdam William Andrew, 2016)
Nanobiomaterials in Medical Imaging presents the latest developments in medical exploratory approaches using nanotechnology. Leading researchers from around the world discuss recent progress and state-of-the-art techniques. The book covers synthesis and surface modification of multimodal imaging agents, popular examples of nanoparticles and their applications in different imaging techniques, and combinatorial therapy for the development of multifunctional nanocarriers. The advantages and potential of current techniques are also considered. This book will be of interest to postdoctoral researchers, professors and students engaged in the fields of materials science, biotechnology and applied chemistry. It will also be highly valuable to those working in industry, including pharmaceutics and biotechnology companies, medical researchers, biomedical engineers and advanced clinicians.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Nanostructured materials; Biomedical materials; Diagnostic imaging; Electronic books